2021
DOI: 10.9734/jpri/2021/v33i47b33151
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Review on the Pathogenicity of Plasmodium berghei in the Liver and Spleen of the Experimental Mice

Abstract: Malaria is still one of the most prevalent tropical and parasitic diseases throughout the world representing a global health concern. Even with all efforts to restrict disease transmission and national malaria control programs, malaria infection continues to cause considerable morbidity and mortality in resource-poor countries. Malaria infection occurs in two stages, the Exoerythrocytic and Erythrocytic stage. The exact biology of malaria parasite in human hosts is likely relatively similar, with the main diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
2
1
0
Order By: Relevance
“…A significant reduction in the total number of RBCs in the P. berghei –infected mice observed in this study. This investigation is in agreement with former finding revealing the elimination of the red blood cells by the spleen as a result of P. berghei infection (Albohiri & Alzanbagi, 2021). Hemoglobin is the iron‐containing oxygen‐transport metalloprotein present in RBCs of animals and its role is to transport oxygen to tissues for the oxidation of ingested food in order to liberate energy for normal functioning of the biological system.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A significant reduction in the total number of RBCs in the P. berghei –infected mice observed in this study. This investigation is in agreement with former finding revealing the elimination of the red blood cells by the spleen as a result of P. berghei infection (Albohiri & Alzanbagi, 2021). Hemoglobin is the iron‐containing oxygen‐transport metalloprotein present in RBCs of animals and its role is to transport oxygen to tissues for the oxidation of ingested food in order to liberate energy for normal functioning of the biological system.…”
Section: Discussionsupporting
confidence: 94%
“…A signi cant reduction in the total number of red blood cells (RBCs) in the P. berghei -infected mice observed in this study revealed detrimental signs of severe anaemia which is a core clinical indication of complicated malaria in patients (Keating et al, 2021). This investigation is in agreement with former nding revealing the elimination of the red blood cells by the spleen as a result of P. berghei infection (Albohiri and Alzanbagi, 2021). Malaria parasite infection causes the destruction of red blood cells (erythrocytes), known as haemolysis as well as the defective development of erythrocytes, known as dyserythropoesis (Thakur et al, 2020), which prevents quick recuperation from anemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation